Microplastics in aquatic ecosystems: Detection, source tracing, and sustainable management strategies - Wu, Baihui; Yu, Haiyang; Lei, Pengyu; He, Jiaxuan; Yi, Jia; Wu, Wei; Wang, Hanbing; Yang, Qinsi; Zeng, Guoming; Sun, Da (Ecotoxicology and environmental safety, 2025)
Microplastics (MPs) are emerging contaminants characterized by persistence, cross-media transport, and complex pollutant interactions, posing serious ecotoxicological risks to ecosystems and human health. Effective MPs management requires multi-faced, long-term, strategies involving targeted sampling, quantitative detection, and comprehensive risk assessments, all of which entail significant resource investment. Despite advancements in remediation technologies, a holistic governance framework integrating these innovations remains underdeveloped. This review synthesizes current knowledge on MPs, elaborating on their diverse morphologies, degradation pathways, and their role as vectors for toxic substances. State-of-the-art extraction techniques are evaluated in this article, including micropore adsorption using nanocomposites, alongside the incorporation of advanced analytical tools such as spectroscopic methods, electron microscopy, and bioinformatics to augment environmental forensics. This review also underscores the necessity of formulating robust global policies to regulate MPs pollution and discusses the potential of biodegradation and thermal degradation as sustainable solutions for MPs removal. By promoting an interdisciplinary approach, this review advocates for a coordinated global response, integrating environmental science, policy frameworks, and waste management strategies to mitigate the escalating impact of MPs on ecosystems and human well-being. [Display omitted] •Environmental forensics enables targeted tracing of MPs pollution sources.•Standardized forensic investigations enhance MPs pollution assessments.•Advanced detection techniques improve MPs identification and risk analysis.•Biodegradation and thermal treatment offer sustainable MPs remediation.•Global policies and interdisciplinary strategies are key to MPs control.